Ashy dermatosis with a Wagyu beef‐like dermoscopic appearance: Report of two cases. Issue 1 (20th November 2022) - Munekata, Yuki; Yanagi, Teruki; Shimano, Mayuna; Orita, Akihiro; Shiiya, Chihiro; Kitamura, Shinya; Ujiie, Hideyuki
Abstract: There have been no reports as to the link between dermoscopic observations and disease activity in ashy dermatosis. We herein report two cases of ashy dermatosis displaying on dermoscopy the so‐called Wagyu beef‐like pattern, consisting of pigmentation on skin rete ridges and brown dots. Ashy dermatosis histologic features may change according to the clinical activity of the eruption; both of our cases were deemed to be in late stages, histopathologically characterized by dermal melanin incontinence without vacuolization of the basal cell layer. The present cases suggest that the Wagyu beef‐like appearance can be seen even in late stages of activity in ashy dermatosis.